Ecology and Pathology of Novel Plaque-Like Growth Anomalies Affecting a Reef-Building Coral on the Great Barrier Reef - Kelly, Lisa A.; Heintz, Tom; Lamb, Joleah B.; Ainsworth, Tracy D.; Willis, Bette L. (Frontiers in Marine Science, 2016)
Here we identify ecological and structural characteristics of a novel plaque-like growth anomaly (GA) at outbreak levels in a population of the staghorn coral, Acropora muricata, on the Great Barrier Reef. The smooth appearance of the plaques results from thickening of skeletal structures comprising the coenosteum, leading to infilling of spaces between corallites, and was associated with hyperplasia and hypertrophy of calicodermal cells. This resulted in a 2-fold reduction in corallite height, a 1.6-fold increase in corallite width, and a 2.3-fold increase in the thickness of the calicodermal layer compared to healthy corallites. Plaque-like GAs affected ~67% of corals surveyed, and on average, encased 50% of the surface area of diseased branches. Progression rates along branches averaged 0.22mm day-1 over a 2.5-month period. GAs spread throughout colonies but their presence did not affect the linear extension rates of branches. Reproductive products were absent in 55% of GA tissues, and when present, mean oocyte and spermary numbers were reduced by 50%. However, when present, mean sizes of oocytes and spermaries did not differ between healthy and GA tissues. Symbiodinium densities were also reduced by 50% in polyps within GA tissues, which were characterized by an absence of polyp structure and chaotic arrangement of gastrovascular canals, compromising host nutrition. A 3-fold increase in stores of the immune-related precursor, prophenoloxidase, within GA tissues compared to healthy tissue suggests a primed immune response. Concomitantly, only 35% of prophenoloxidase was converted to the active enzyme phenoloxidase compared to 81% in healthy tissues, consistent with inhibition of immune-related enzymatic reactions by an unknown causative agent. The increasing frequency of emerging disease hotspots highlights the importance of understanding sublethal effects of diseases that have important implications for the fitness and long-term resilience of coral populations.